THE NATURE AND LAWS OF THE LEARNING PROCESS - N. Mullasodiqova (Galaxy International Interdisciplinary Research Journal, 2021)
One of the main parts of didactics is the part of teaching principles. Principles of teaching are the basic rules that determine the nature of a teacher’s activities and students ’learning activities. Ignorance of these principles or inaccuracies in their application impede the work of teaching, impede the acquisition of knowledge, the formation of qualities that affect the personality of students.